The Future of Teacher Training in a Tech-Driven-Driven Education Landscape - Ragab, Aya; Ahmed, Ohod Faisal; Sayed, Ahmed Khamis (LPPM Universitas Bina Bangsa, 2024)
The rapid advancement of technology has created a new challenge for teacher training: bridging the digital divide. This qualitative study, conducted at Universitas Sebelas Maret and Universitas Muhammadiyah Surakarta in Indonesia, explores this gap through the lens of pre-service teachers and faculty. Through semi-structured interviews and focus group discussions, the study uncovers the complexities of this transition, revealing a critical need for enhanced digital literacy, expanded access to resources, and robust institutional support. For instance, many pre-service teachers expressed feelings of being overwhelmed by the sheer volume of new technologies and lacked confidence in their ability to effectively integrate them into their future classrooms. The study also revealed a significant gap between the availability of technology and the capacity of pre-service teachers to use it effectively. While many universities provided access to computers and internet, they often lacked the necessary infrastructure and training to support teachers in developing their digital skills. This research highlights the urgent need for a more responsive approach to teacher training in the digital age, one that empowers educators to effectively embrace technology while nurturing a love for learning in their students. By creating a more robust teacher training ecosystem that addresses the unique challenges of a tech-driven education landscape, we can ensure that all students have access to high-quality, engaging, and equitable learning experiences.